2019
DOI: 10.1038/s41598-019-42757-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel DNA Biosensor for Direct Determination of Carrageenan

Abstract: A novel disposable electrochemical biosensor based on immobilized calf thymus double-stranded DNA (dsDNA) on the carbon-based screen-printed electrode (SPE) is developed for rapid biorecognition of carrageenan by using methylene blue (MB) redox indicator. The biosensor protocol for the detection of carrageenan is based on the concept of competitive binding of positively charged MB to the negatively charged dsDNA and carrageenan. The decrement in the MB cathodic peak current ( i pc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Other researchers have previously reported similar negative impact of salt on MB-DNA interactions and intercalation 33 , 34 . The cation binds with the negative phosphate backbone of DNA thereby hindering the electrostatic interactions between MB and DNA 35 . At higher DNA concentrations, steric inhibition of redox active MB causes reduction in peak current, and therefore electrostatic interactions do not significantly influence the sensor response.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers have previously reported similar negative impact of salt on MB-DNA interactions and intercalation 33 , 34 . The cation binds with the negative phosphate backbone of DNA thereby hindering the electrostatic interactions between MB and DNA 35 . At higher DNA concentrations, steric inhibition of redox active MB causes reduction in peak current, and therefore electrostatic interactions do not significantly influence the sensor response.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods for detecting carrageenan in food have been described in the literature. These include, for example, colorimetric methods [17,48,49]. Soedjak [50] detected carrageenan in milk photometrically with the addition of methylene blue.…”
Section: Validation Of the Methods On Samples From The Retail Marketmentioning
confidence: 99%
“…DNA can form various nanoscale structures; recently, many a research has been conducted on biosensors using DNA. [1][2][3] DNA is known to pass electric current under certain conditions, 4 and a number of research groups reported on evaluation of DNA electric characteristics. [5][6][7][8] In addition, a device was proposed to detect deoxyribonuclease (DNase) by measuring impedance change in λDNA stretched and immobilized between opposing triangularshaped electrodes.…”
Section: Forewordmentioning
confidence: 99%
“…DNA can form various nanoscale structures; recently, many a research has been conducted on biosensors using DNA 1–3 . DNA is known to pass electric current under certain conditions, 4 and a number of research groups reported on evaluation of DNA electric characteristics 5–8 .…”
Section: Forewordmentioning
confidence: 99%